THE EXPANSION OF CENTER-PIVOT IRRIGATION IN THE CERRADO BIOME - Althoff, Daniel; Rodrigues, Lineu Neiva (IRRIGA, 2019)
THE EXPANSION OF CENTER-PIVOT IRRIGATION IN THE CERRADO BIOME DANIEL ALTHOFF1 AND LINEU NEIVA RODRIGUES2 1 Department of Agricultural Engineering, Federal University of Viçosa (UFV), Avenue Peter Henry Rolfs, s/n – University Campus, 36570-900, MG, Brazil. daniel.althoff@ufv.br. 2 Brazilian Agricultural Research Corporation (EMBRAPA)- Cerrados, BR-020, Km-18, 73310-970, Planaltina, DF, Brazil. lineu.rodrigues@embrapa.br. 1 ABSTRACT In the Cerrado biome, irrigation plays a key role in food production and local socio-economic development. In this region, with general gentle topography and large areas planted with annual crops, center pivot, for its automation and uniformity in water application, is the preferred irrigation system, In the last two decades, the Cerrado region has concentrated roughly 80% of all center pivots installed in the Brazilian territory. The region alone has a potential irrigation area of 26.5 Mha and as so it is expected that center pivot irrigation continues increasing. By considering the average trend from recent years until 2050, irrigated area in the Cerrado will still be short from the potential area classified as high priority for irrigation expansion (6.3 Mha). However, as many of these areas are considered of maximum interest for public intervention, the increase trends could be higher than expected. Keywords: agricultural water use, irrigation demand, water balance. ALTHOFF, D.; RODRIGUES, L. N. A EXPANSÃO DA IRRIGAÇÃO POR PIVÔS CENTRAIS NO CERRADO 2 RESUMO A irrigação desempenha um papel fundamental na produção de alimento e desenvolvimento socioeconômico local no Cerrado. Nessa região, com topografia geralmente plana e grandes áreas plantadas com culturas anuais, o pivô central, por sua automação e uniformidade de aplicação, é o sistema de irrigação mais utilizado. Nas as últimas duas décadas a região do Cerrado tem concentrado aproximadamente 80% de todos pivôs centrais do Brasil. Somente nessa região potencial de área irrigada chega aos 26.5 Mha e, dessa forma, é esperado que áreas irrigadas por pivôs centrais continuem a crescer. Mesmo considerando a projeção de crescimento médio de áreas irrigadas dos últimos anos até o ano de 2050, a área total irrigada ficará distante do número classificado como alta prioridade em expansão da irrigação (6.3 Mha). Contudo, como muitas dessas áreas são consideradas de máximo interesse para intervenção pública, as tendências podem ser maiores que as esperadas. Palavras-chave: uso da água na agricultura, demanda de irrigação, balanço hídrico.